Thermal-wear-resistant high-propylene-yield catalytic cracking catalytic promoter and preparation method thereof, and hydrocarbon oil catalytic cracking method

By using MFI molecular sieve, phosphorus-aluminum binder and other constituent materials in the catalytic cracking catalyst, a catalytic cracking catalyst that is resistant to heat wear is solved, and the effects of high yield, optimization and low coke generation are achieved.

CN119909730AActive Publication Date: 2025-05-02CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311435172.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-05-02
Estimated Expiration
2043-10-31

AI Technical Summary

Technical Problem

The thermal wear performance of existing catalytic cracking catalysts is poor, resulting in low yield and selectivity of catalytic cracking liquefied gas and propylene, and more coke generation.

Method used

A catalytic cracking catalyst additive that is resistant to heat wear is used, which is composed of MFI molecular sieve, phosphorus aluminum binder, silicon aluminum inorganic binder, first aluminum-based binder and clay. The thermal wear performance of the catalyst is improved through specific composition ratios and preparation methods.

Benefits of technology

The yield and selectivity of catalytic cracking liquefied gas and propylene are significantly improved, coke generation is reduced, and the wear resistance of the catalyst is improved, especially the thermal wear performance under high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119909730A_ABST
    Figure CN119909730A_ABST
Patent Text Reader

Abstract

The invention relates to a thermal-wear-resistant high-propylene-yield catalytic cracking catalytic promoter and a preparation method thereof, and a hydrocarbon oil catalytic cracking method, based on the dry basis weight of the catalytic cracking catalytic promoter, the catalytic cracking catalytic promoter comprises 10-75 wt% of an MFI molecular sieve, 3-35 wt% of a phosphorus-aluminum binder (calculated as P2O5 and Al2O3), 1-5 wt% of a catalyst, and the balance of a solvent. The content of the silicon-aluminum inorganic binder in terms of SiO2 and Al2O3 is 1-20% by weight, the content of the first aluminum-based binder in terms of Al2O3 is 0-15% by weight, and the content of the clay is 0-50% by weight. The catalytic cracking catalytic promoter disclosed by the invention has relatively high wear resistance, especially hot grinding performance, has good catalytic activity, can effectively increase the yield of catalytic cracking liquefied gas and propylene, is high in propylene selectivity and conversion rate, and reduces coke at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a heat-wear-resistant catalytic cracking catalyst aid for producing more propylene, a preparation method thereof, and a method for catalytic cracking of hydrocarbon oil. Background Art

[0002] As a very important basic organic chemical raw material, the demand for propylene continues to grow. Catalytic cracking units are based on a wider source of raw materials and lower operating costs, and it is more economical and convenient to increase the production of propylene. For most catalytic cracking units, adding additives is an effective technical approach to increase the production of light olefins, and the acidity of the catalyst and the shape selectivity of the pores determine the yield of light olefins in the product.

[0003] The prior art discloses a five-membered ring high-silicon zeolite catalyst for light olefins in a fluidized catalytic device, the catalyst comprising (a) a five-membered ring high-silicon zeolite, (b) 8-24 wt% of phosphorus, as measured by P 2 O 5 1-10 wt% of iron oxide, based on particles of pentasilica-containing zeolite, as Fe 2 O 3 The catalyst is fluidizable and has an average particle size of about 20 to about 200 microns. The catalyst composition can improve the yield of light olefins such as propylene in a fluidized catalytic cracking (FCC) process. A cracking aid for improving propylene concentration is disclosed in the prior art, which is composed of 10-65% by weight of a modified ZSM-5 molecular sieve, 0-60% by weight of clay, 15-60% by weight of an inorganic oxide binder, 0.5-15% by weight of one or more metal additives selected from the metals of Group VIIIB and 2-25% by weight of a phosphorus additive, wherein the modified ZSM-5 molecular sieve is modified by phosphorus and a metal selected from one of Fe, Co or Ni, and its anhydrous chemical expression is (0-0.3)Na in terms of oxide. 2 O·(0.5-5)Al 2 O 3 (1.3-10)P 2 O 5 ·(0.7-15)M x O y ·(70-97)SiO 2 , x represents the number of atoms of M, y represents a number required to satisfy the oxidation state of M, and the metal additive and phosphorus additive are both calculated in terms of oxides. The cracking aid is applied to the catalytic cracking process of petroleum hydrocarbons, and can significantly increase the propylene concentration in the liquefied gas while increasing the yield of catalytic cracking liquefied gas and the octane number of catalytic cracking gasoline. However, in the prior art, due to the phosphorus-aluminum binder content in the matrix, the thermal grinding strength of the catalyst has always been relatively poor. Summary of the invention

[0004] The purpose of the present invention is to provide a catalytic cracking catalyst promoter and a preparation method thereof and a method for catalytic cracking of hydrocarbon oil. The catalytic cracking catalyst promoter disclosed in the present invention has high wear resistance, especially thermal wear resistance, and can effectively increase the yield of catalytic cracking liquefied gas and propylene, improve propylene selectivity and conversion rate, and reduce coke.

[0005] In order to achieve the above-mentioned object, the first aspect of the present disclosure provides a heat-resistant and wear-resistant catalytic cracking catalyst promoter for producing more propylene, wherein the catalytic cracking catalyst promoter contains an MFI molecular sieve, a phosphorus aluminum binder, a silicon aluminum inorganic binder, a first aluminum-based binder and clay;

[0006] Based on the dry weight of the catalytic cracking catalyst promoter, the content of the MFI molecular sieve is 10-75% by weight, based on the dry weight of the catalytic cracking catalyst promoter. 2 O 5 and Al 2 O 3 The content of the phosphorus aluminum binder is 3-35% by weight, and the content of SiO 2 and Al 2 O 3 The content of the silicon-aluminum inorganic binder is 1-20% by weight, and the content of Al 2 O 3 The content of the first aluminum-based binder is 0-15% by weight, and the content of the clay is 0-50% by weight;

[0007] The weight of the phosphorus-aluminum binder is taken as the basis, and the phosphorus-aluminum binder contains 3-15 weight % of Al 2 O 3 , 15-40 wt% P 2 O 5 and 0.1-10 wt% of a stabilizer; the phosphorus aluminum binder has a P / Al weight ratio of 1.6-6, a pH value of 0.5-2.5, and a QP 0 2 / QP 0 0 is 1-5, where QP 0 2 Indicated by 31 The chemical shift of the aluminum-phosphorus binder obtained by nuclear magnetic resonance spectroscopy is 12±2ppm, QP 0 0 Indicates the resonance signal peak area with a chemical shift of 0±2ppm; the average particle size of the phosphorus aluminum binder is 10-30nm;

[0008] The silicon-aluminum inorganic binder is obtained by reacting a second aluminum-based binder and a silicon-based binder in a weight ratio of (1-50):1, wherein the second aluminum-based binder is Al2 O 3 The silicon-based binder is SiO 2 count.

[0009] Optionally, the straight tube wear index of the catalytic cracking catalyst promoter is 0-2% / h; and the thermal wear index is 0-8% / h.

[0010] Optionally, based on the dry weight of the catalytic cracking catalyst promoter, the content of the MFI molecular sieve is 15-65% by weight, based on the dry weight of the catalytic cracking catalyst promoter. 2 O 5 and Al 2 O 3 The content of the phosphorus-aluminum binder is 8-32% by weight, the content of the first aluminum-based binder is 2-10% by weight, and the content of the clay is 1-20% by weight.

[0011] Optionally, the aluminum phosphorus binder contains 3-12 wt% Al 2 O 3 , 15-32 wt% P 2 O 5 and 0.5-5 wt% of a stabilizer, the phosphorus aluminum binder has a P / Al weight ratio of 1.7-5.8, a pH value of 0.5-2.5, and QP 0 2 / QP 0 0 It is 1.5-5.

[0012] Optionally, the first aluminum-based binder and the second aluminum-based binder are independently selected from one or more of pseudo-boehmite, acidified aluminum stone and aluminum sol; the silicon-based binder is acidic silica sol;

[0013] The clay is selected from one or more of kaolin, sepiolite, attapulgite, rectorite, montmorillonite and diatomaceous earth;

[0014] The MFI molecular sieve is one or more of a hydrogen-type MFI molecular sieve, a phosphorus-containing MFI molecular sieve and a transition metal-containing MFI molecular sieve.

[0015] The second aspect of the present disclosure provides a method for preparing the catalytic cracking catalyst promoter provided by the first aspect of the present disclosure, the method comprising:

[0016] S1, mixing and slurrying the second aluminum-based binder and the silicon-based binder, and aging at 50-90° C. for 30-60 min to obtain a silicon-aluminum inorganic binder;

[0017] S2, mixing and slurrying the silica-alumina binder, MFI molecular sieve, optional first aluminum-based binder, optional clay and water, controlling the pH value of the obtained first slurry to be 2-5, to obtain a second mixture;

[0018] S3, mixing the second mixture with a phosphorus aluminum binder and slurrying, spray drying and calcining the obtained second slurry to obtain the catalytic cracking catalyst promoter.

[0019] Optionally, the aluminum-phosphorus binder is prepared by a method comprising the following steps:

[0020] (1) mixing an aluminum source, water and a stabilizer at a temperature of 50-95° C. and stirring to obtain an aluminum oxide precursor solution having a solid content of 5-40% by weight;

[0021] (2) Mixing and reacting the alumina precursor solution with phosphate at a temperature of 25-70° C. and under stirring conditions to obtain the phosphate-aluminum binder.

[0022] Optionally, the aluminum source is selected from one or more of aluminum nitrate, aluminum sulfate and aluminum chloride;

[0023] The phosphate is diammonium hydrogen phosphate and / or ammonium dihydrogen phosphate;

[0024] The stabilizer is selected from one or more of acetic acid, glycolic acid, oxalic acid, malonic acid, malic acid, tartaric acid, succinic acid, adipic acid, maleic acid, itaconic acid and citric acid, preferably acetic acid or citric acid.

[0025] A third aspect of the present disclosure provides a method for catalytic cracking of hydrocarbon oil, the method comprising: contacting the hydrocarbon oil with a catalyst for reaction, wherein the catalyst contains the catalytic promoter provided by the first aspect of the present disclosure.

[0026] Optionally, the conditions for the hydrocarbon oil catalytic cracking reaction include: a temperature of 400-600°C, a weight hourly space velocity of 8-120 hours -1 , the agent-oil weight ratio is 1-20.

[0027] Through the above technical scheme, the catalytic cracking catalyst promoter disclosed in the present invention has high wear resistance, especially thermal wear resistance, wherein the synergistic effect of the phosphorus aluminum binder, the silicon aluminum inorganic binder and the MFI molecular sieve enables the catalytic cracking catalyst promoter to effectively increase the yield of catalytic cracking liquefied gas and propylene, with high propylene selectivity, high conversion rate and low coke.

[0028] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:

[0030] Figure 1 The NMR spectrum of the prepared aluminum-phosphorus binder and the NMR spectrum of the aluminum-phosphorus binder prepared in Comparative Example 1. DETAILED DESCRIPTION

[0031] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.

[0032] The first aspect of the present disclosure provides a heat-resistant and wear-resistant catalytic cracking catalyst promoter for producing more propylene, wherein the catalytic cracking catalyst promoter contains an MFI molecular sieve, a phosphorus aluminum binder, a first inorganic binder and clay;

[0033] Based on the dry weight of the catalytic cracking catalyst promoter, the content of the MFI molecular sieve is 10-75% by weight, based on the dry weight of the catalytic cracking catalyst promoter. 2 O 5 and Al 2 O 3 The content of the phosphorus aluminum binder is 3-35% by weight, and the content of SiO 2 and Al 2 O 3 The content of the silicon-aluminum inorganic binder is 1-20% by weight, and the content of Al 2 O 3 The content of the first aluminum-based binder is 0-15% by weight, and the content of the clay is 0-50% by weight;

[0034] The weight of the phosphorus-aluminum binder is taken as the basis, and the phosphorus-aluminum binder contains 3-15 weight % of Al 2 O 3 , 15-40 wt% P 2 O 5 and 0.1-10 wt% of a stabilizer; the phosphorus aluminum binder has a P / Al weight ratio of 1.6-6, a pH value of 0.5-2.5, and a QP 0 2 / QP 0 0 is 1-5, where QP 0 2 Indicated by 31 The chemical shift of the aluminum-phosphorus binder obtained by nuclear magnetic resonance spectroscopy is 12±2ppm, QP 0 0Indicates the resonance signal peak area with a chemical shift of 0±2ppm; the average particle size of the phosphorus aluminum binder is 10-30nm;

[0035] The silicon-aluminum inorganic binder is obtained by reacting a second aluminum-based binder and a silicon-based binder in a weight ratio of (1-50):1, wherein the second aluminum-based binder is Al 2 O 3 The silicon-based binder is SiO 2 count.

[0036] In the present disclosure, the first aluminum-based binder refers to other aluminum-based binders except the phosphorus aluminum binder and the silicon aluminum inorganic binder, and the first aluminum-based binder is directly used to prepare the auxiliary agent of the present application. The second aluminum-based binder is directly used to prepare the silicon aluminum inorganic binder and indirectly used to prepare the auxiliary agent of the present application.

[0037] The catalytic cracking catalyst promoter disclosed in the present invention contains a specific phosphorus-aluminum binder, which has less free phosphate and more polymerized phosphate, good bonding performance and long service life. When used in combination with a silicon-aluminum inorganic binder, the catalyst's wear resistance, especially thermal wear, can be significantly improved, and the reaction with matrix aluminum and aluminum on the MFI molecular sieve can be reduced, thereby improving the strength of the catalyst and retaining more active centers of the molecular sieve. The synergistic effect among the phosphorus-aluminum binder, the silicon-aluminum inorganic binder and the molecular sieve disclosed in the present invention makes the catalytic cracking catalyst promoter have better wear resistance, can effectively increase the yield of catalytic cracking liquefied gas and propylene, improve propylene selectivity and conversion rate, and reduce coke formation.

[0038] According to the present disclosure, the average particle size of the phosphate-aluminum binder is detected by a transmission electron microscopy method, specifically, the phosphate-aluminum binder is subjected to a transmission electron microscopy analysis, 100 phosphate-aluminum binder particles are randomly selected from the TEM photo and their maximum diameters are respectively measured as their particle sizes, and the average value of the particle sizes of the 100 phosphate-aluminum binder particles is calculated, which is the average particle size.

[0039] In a specific embodiment of the present disclosure, the straight tube wear index of the catalytic cracking catalyst is 0-2% / h; the thermal wear index is 0-8% / h. In the present disclosure, the straight tube wear index determination method refers to Sinopec Q / SH 361909-2018, specifically, a certain amount of sample is placed in a wear index determination device and blown for five hours at a constant gas velocity. The sample blown out in the first hour is discarded, and the sample blown out in the last four hours is collected to calculate the average wear percentage per hour (the weight of the sample less than 15 microns blown out per hour accounts for the percentage of the weight of the catalyst greater than 15 microns), which is called the catalyst wear index. The smaller the wear index, the better the anti-wear performance of the catalyst. In the present disclosure, under the conditions of 700°C, a gas velocity of 10L / min, and a wear time of 5h, the fine powder generated by the friction and collision between the catalyst particles and the catalyst and the wall is brought into the collector by the airflow, and the thermal wear index of the catalyst is obtained by calculating the amount of solids lost per unit time.

[0040] In a specific embodiment of the present disclosure, based on the dry weight of the catalytic cracking catalyst promoter, the content of the MFI molecular sieve is 15-65% by weight, based on the dry weight of the catalytic cracking catalyst promoter. 2 O 5 and Al 2 O 3 The content of the phosphorus aluminum binder is 8-32% by weight, and the content of SiO 2 and Al 2 O 3 The content of the silicon-aluminum inorganic binder is 2-20% by weight, the content of the first aluminum-based binder is 2-10% by weight, and the content of the clay is 1-20% by weight. Preferably, based on the dry weight of the catalytic cracking catalyst promoter, the content of the MFI molecular sieve is 20-60% by weight, and the content of the P is 1-20% by weight. 2 O 5 and Al 2 O 3 The content of the phosphorus aluminum binder is 10-30% by weight, and the content of SiO 2 and Al 2 O 3 The content of the silicon-aluminum inorganic binder is 10-18% by weight, the content of the first aluminum-based binder is 2-10% by weight, and the content of the clay is 5-18% by weight.

[0041] In a specific embodiment of the present disclosure, the phosphorus aluminum binder contains 3-12 wt% Al 2 O 3 , 15-32 wt% P 2 O 5and 0.5-5 wt% of a stabilizer, the phosphorus aluminum binder has a P / Al weight ratio of 1.7-5.8, a pH value of 0.5-2.5, and QP 0 2 / QP 0 0 It is 1.5-5.

[0042] In a specific embodiment of the present disclosure, the first aluminum-based binder and the second aluminum-based binder are each independently selected from one or more of pseudo-boehmite, acidified aluminum stone and aluminum sol; and the silicon-based binder is acidic silica sol.

[0043] According to the present disclosure, clay can be commonly used by those skilled in the art in preparing catalysts. In a specific embodiment of the present disclosure, the clay is selected from one or more of kaolin, sepiolite, attapulgite, rectorite, montmorillonite and diatomaceous earth.

[0044] In a specific embodiment of the present disclosure, the MFI molecular sieve is one or more selected from hydrogen-type MFI molecular sieve, phosphorus-containing MFI molecular sieve and transition metal-containing MFI molecular sieve.

[0045] The second aspect of the present disclosure provides a method for preparing the catalytic cracking catalyst promoter provided by the first aspect of the present disclosure, the method comprising: S1, mixing and slurrying a second aluminum-based binder and a silicon-based binder, and aging at 50-90°C for 30-60min to obtain a silicon-aluminum inorganic binder; S2, mixing and slurrying the silicon-aluminum inorganic binder, MFI molecular sieve, an optional first aluminum-based binder, an optional clay and water, and controlling the pH value of the obtained first slurry to be 2-5 to obtain a second mixture; S3, mixing and slurrying the second mixture and a phosphorus-aluminum binder, and spray-drying and calcining the obtained second slurry to obtain the catalytic cracking catalyst promoter.

[0046] The method disclosed in the present invention can prepare a catalytic cracking catalyst promoter with better catalytic performance. The catalytic cracking catalyst promoter has better wear resistance, especially better thermal grinding performance, and can effectively increase the yield of catalytic cracking liquefied gas and propylene, with high propylene selectivity, high conversion rate and low coke.

[0047] In a specific embodiment of the present disclosure, in step S2, the MFI molecular sieve, the silica-alumina inorganic binder, the clay and water are first mixed and slurried, and then the first aluminum-based binder is added to the obtained mixture for mixing and slurrying to obtain the first slurry, which is beneficial to further improve the activity and strength of the catalytic cracking catalyst.

[0048] According to the present disclosure, spray drying is a technical means well known to those skilled in the art, and the specific method is not repeated here. In a specific embodiment, the inlet temperature of spray drying can be 300-700°C, and the outlet temperature can be 80-200°C.

[0049] In a specific embodiment of the present disclosure, the calcination temperature is 400-700° C., preferably 450-600° C., and the calcination time is 0.5-100 hours, preferably 0.5-10 hours.

[0050] In a specific embodiment of the present disclosure, the phosphoaluminum binder is prepared by a method comprising the following steps: (1) mixing an aluminum source, water and a stabilizer at a temperature of 50-95°C and under stirring to obtain an alumina precursor solution with a solid content of 5-40 wt%; (2) mixing and reacting the alumina precursor solution with a phosphate at a temperature of 25-70°C and under stirring to obtain the phosphoaluminum binder.

[0051] The phosphate-aluminum binder used in the method disclosed in the present invention is prepared from low-cost aluminum salt and phosphate, has less free phosphate and more polymerized phosphate, and has good bonding performance. The stabilizer contained in the phosphate-aluminum binder can effectively extend the service life of the phosphate-aluminum binder.

[0052] In a specific embodiment of the present disclosure, in step (1), the weight ratio of the aluminum salt, water and stabilizer is 100:(50-800):(5-40), preferably 100:(100-750):(6-35), and the aluminum salt is calculated as aluminum oxide; in step (2), the weight ratio of the aluminum oxide precursor solution to the phosphate is 100:(50-200), preferably 100:(60-150), and the phosphate is calculated as phosphorus oxide.

[0053] In a specific embodiment of the present disclosure, the aluminum source is selected from one or more of aluminum nitrate, aluminum sulfate and aluminum chloride; the phosphate is diammonium hydrogen phosphate and / or ammonium dihydrogen phosphate; the stabilizer is selected from one or more of acetic acid, glycolic acid, oxalic acid, malonic acid, malic acid, tartaric acid, succinic acid, adipic acid, maleic acid, itaconic acid and citric acid, preferably acetic acid or citric acid.

[0054] A third aspect of the present disclosure provides a method for catalytic cracking of hydrocarbon oil, the method comprising: contacting the hydrocarbon oil with a catalyst for reaction, wherein the catalyst contains the catalytic promoter provided by the first aspect of the present disclosure.

[0055] In a specific embodiment of the present disclosure, the catalyst is a mixture of the catalyst promoter provided in the first aspect of the present disclosure and an optional main catalyst, and the reaction is a catalytic cracking reaction of hydrocarbon oil. According to the present disclosure, the main catalyst can be selected according to actual needs. In a specific embodiment of the present disclosure, the main catalyst can be selected from a catalytic cracking catalyst and / or a catalytic cracking catalyst, for example, it can include but is not limited to one or more of RFCC catalyst, CGP catalyst, GOR olefin reduction catalyst and DCC catalyst.

[0056] In a specific embodiment of the present disclosure, the conditions for the catalytic cracking reaction of hydrocarbon oil include: a temperature of 400-600°C, preferably 450-550°C, a weight hourly space velocity of 8-120 hours -1 , preferably 8-80 hours -1 , the catalyst-oil weight ratio is 1-20, preferably 3-15. The catalytic cracking catalyst promoter provided by the present disclosure can be used in various existing catalytic cracking reactors, such as fixed bed reactors, fluidized bed reactors, riser reactors, multi-reaction zone reactors, etc.

[0057] The present disclosure is further illustrated below by way of examples, but the present disclosure is not limited thereby.

[0058] When the catalytic cracking catalyst disclosed in the present invention is used for evaluating the performance of catalytic cracking reactions, an ACE device is used for evaluation.

[0059] The RIPP standard method described in the present disclosure can be specifically found in "Petrochemical Analysis Methods", edited by Yang Cuiding et al., 1990 edition.

[0060] For the determination method of straight tube wear strength, please refer to Sinopec Q / SH 361 909-2018.

[0061] The thermal wear index is detected by the following method: under the conditions of 700°C, a gas velocity of 10L / min and a wear time of 5h, the fine powder generated by the friction and collision between the catalyst particles and between the catalyst and the wall is carried into the collector by the airflow, and the thermal wear index of the catalyst is obtained by calculating the amount of solid lost per unit time.

[0062] The pore volume was determined by nitrogen adsorption method (RIPP151-90).

[0063] The properties of some of the raw materials used in the embodiments and comparative examples are as follows:

[0064] Pseudo-boehmite is an industrial product produced by Shandong Aluminum Company, with a solid content of 60% by weight;

[0065] Alumina sol is an industrial product produced by Sinopec Catalyst Qilu Branch. 2 O 3The content is 21.5% by weight;

[0066] The kaolin is kaolin specially used for catalytic cracking catalyst produced by Suzhou Kaolin Company, and has a solid content of 78% by weight.

[0067] Hydrochloric acid: chemically pure, concentration 36-38% by weight, produced by Beijing Chemical Plant.

[0068] ZSP molecular sieve: industrial product produced by Sinopec Catalyst Qilu Branch, P 2 O 5 The content is 3.25% by weight, Fe 2 O 3 The content is 1.85% by weight and the crystallinity is 75%.

[0069] Silica sol: SiO 2 The solid content is 30% by weight and the pH value is 2.

[0070] The average particle size of the phosphorus aluminum binder disclosed in the present invention is detected by transmission electron microscopy.

[0071] Preparation Examples 1-4 are preparation examples of the phosphoaluminum binder disclosed in the present invention.

[0072] Preparation Example 1

[0073] (1) 0.56 kg of anhydrous aluminum sulfate, 0.25 kg of deionized water, and 0.05 kg of oxalic acid were mixed and stirred, and the mixture was heated to 70° C. and slurried for 30 minutes to obtain an aluminum oxide precursor having a solid content of 39 wt %;

[0074] (2) Control the temperature to 45°C and add 0.56 kg of ammonium dihydrogen phosphate to the alumina precursor prepared in step (1) under stirring, and then react at 45°C for 45 minutes until the mixture becomes a transparent colloid to obtain a phosphorus aluminum binder P-1. The material ratio is shown in Table 1, and the NMR spectrum is shown in Figure 1 .

[0075] Preparation Example 2-4

[0076] The phosphate aluminum binder was prepared by the same method as in Preparation Example 1, except that different raw materials and their amounts were used. The specific material ratios are shown in Table 1.

[0077] Preparation Comparative Example 1

[0078] The inorganic binder containing phosphorus aluminum compound is prepared according to the method provided by patent ZL201110180891.X. The specific method is as follows:

[0079] At room temperature (25°C), 0.98 kg of pseudo-boehmite (containing Al 2 O 30.6kg), 0.26kg of rectorite (dry basis 0.16kg) and 0.44kg of deionized water were mixed and slurried for 30 minutes. 2.01kg of concentrated phosphoric acid (mass concentration 85%) was added to the slurry under stirring. The phosphoric acid addition rate was 0.03kg phosphoric acid / min / kg alumina source. The temperature was raised to 70°C and then reacted at this temperature for 45 minutes to obtain an inorganic binder DPAL-1 containing a phosphorus aluminum compound. The NMR spectrum is shown in Figure 1 .

[0080] Depend on Figure 1 It can be seen that in the 31P NMR spectrum of the phosphorus aluminum binder, the peak area of ​​the resonance signal with a chemical shift of 12±2ppm is defined as QP 0 2 The peak area of ​​the resonance signal with a chemical shift of 0±2ppm is defined as QP 0 0 At the same phosphorus-aluminum ratio, the QP of the phosphorus-aluminum binder prepared in Example 1 is 0 2 / QP 0 0 Compared with the QP of the aluminum-phosphorus binder prepared in Comparative Example 1 0 2 / QP 0 0 Higher, indicating a higher degree of polymerization.

[0081] Table 1

[0082]

[0083]

[0084] Examples 1-6 are preparation examples of catalytic cracking catalyst promoters.

[0085] Example 1

[0086] S1, mixing aluminum sol and acidic silica sol, aging at 75° C. for 40 min to obtain a silicon-aluminum inorganic binder;

[0087] S2, take ZSP molecular sieve, add decationized water and beat for 10 minutes, beat for 120 minutes to obtain molecular sieve slurry; then add molecular sieve slurry, silica-alumina inorganic binder, pseudo-boehmite and kaolin in order, add hydrochloric acid to adjust the pH value of the slurry to 3.0, and then continue beating for 45 minutes to obtain a second mixture;

[0088] S3. The second mixture is mixed with the phosphorus aluminum binder and slurried and stirred for 5 minutes. The obtained slurry is spray dried and the obtained microspheres are calcined at 500° C. for 2 hours to obtain a catalytic cracking catalyst promoter CAT-1. The proportions are shown in Table 3.

[0089] Embodiment 2-6

[0090] The catalytic cracking catalyst promoter was prepared by the same method as in Example 1, except that different raw materials and their amounts were used. The specific ratios are shown in Table 2.

[0091] Comparative Example 1

[0092] Take MPZ molecular sieve, kaolin and aluminum stone, add decationized water and aluminum sol to slurry for 120 minutes, add hydrochloric acid to adjust the pH value of the slurry to 3.0, and then continue to slurry for 45 minutes, then add phosphate aluminum inorganic binder (DPAL-1), stir for 5 minutes, spray dry the obtained slurry to obtain microspheres, calcine the microspheres at 500°C for 1 hour to obtain DCAT-1, and its ratio is shown in Table 2.

[0093] Comparative Example 2

[0094] The catalytic cracking catalyst promoter was prepared by the same method as in Example 2, except that the phosphorus-aluminum inorganic binder DPAL-1 was used instead of the phosphorus-aluminum binder P-1. The material proportions are shown in Table 2.

[0095] Comparative Example 3

[0096] The catalytic cracking catalyst promoter was prepared by the same method as in Example 2, except that in step S1, aluminum sol was directly used as the other inorganic binder instead of mixing and slurrying aluminum sol and silica sol. The material proportions are shown in Table 2.

[0097] Table 2

[0098]

[0099] In Table 2, the ratios are in parts by weight.

[0100] It can be seen from Table 2 that, compared with the reference catalyst, the wear index and thermal wear index of the catalytic cracking catalyst promoter provided by the present disclosure are better than those of the reference catalyst.

[0101] Test Case

[0102] The following examples take a fixed fluidized bed reactor as an example to illustrate the cracking reaction effect of the cracking catalyst provided by the present disclosure.

[0103] Catalytic cracking catalyst SLA and 30g CAT-1-6 and DCAT1-3 were aged for 17 hours at 800°C and 100% steam atmosphere. Different amounts of the aged catalysts were mixed with industrial balance agents (main properties are shown in Table 3), and the catalyst mixture was loaded into the reactor of a small fixed fluidized bed reactor to catalytically crack the crude oil shown in Table 4. Table 5 shows the reaction conditions and reaction results.

[0104] Table 3 Main properties of industrial balancing agents

[0105]

[0106]

[0107] Table 4 Evaluation of the properties of the feedstock oil

[0108] <![CDATA[Density (20 °C), g / cm 3 > 0.92 Carbon residue, % (mass fraction) 4.81 Initial distillation point, ℃ 228.00 500℃ distillation amount, % (volume fraction) 44.50 538℃ distillation amount, % (volume fraction) 54.50 Asphaltene content, % (mass fraction) 1.73 Saturated hydrocarbon content, % (mass fraction) 58.17 Aromatic content, % (mass fraction) 29.01 Gum content, % (mass fraction) 11.10 Total nitrogen, mg / kg 594.30 Iron content, mg / kg 2.16 Sodium content, mg / kg 1.39 Nickel content, mg / kg, ≤10 6.44 Vanadium content, mg / kg, ≤10 8.91

[0109] Table 5 Evaluation results

[0110]

[0111]

[0112] It can be seen from Table 5 that, compared with the reference catalytic cracking catalyst, the catalytic cracking catalyst promoter provided by the present disclosure can effectively increase the yield of catalytic cracking liquefied gas and propylene, with high propylene selectivity, high conversion rate and low coke.

[0113] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0114] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0115] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. A heat-resistant and wear-resistant catalytic cracking catalyst promoter for producing more propylene, the catalytic cracking catalyst promoter comprising MFI molecular sieve, phosphorus aluminum binder, silicon aluminum inorganic binder, first aluminum-based binder and clay; Based on the dry weight of the catalytic cracking catalyst promoter, the content of the MFI molecular sieve is 10-75% by weight, the content of the phosphorus aluminum binder calculated as P2O5 and Al2O3 is 3-35% by weight, the content of the silicon aluminum inorganic binder calculated as SiO2 and Al2O3 is 1-20% by weight, the content of the first aluminum-based binder calculated as Al2O3 is 0.5-15% by weight, and the content of the clay is 0-50% by weight; The weight of the phosphorus-aluminum binder is taken as the basis, and the phosphorus-aluminum binder contains 3-15 weight % of Al2O3, 15-40 weight % of P2O5 and 0.1-10 weight % of a stabilizer; the phosphorus-aluminum binder has a P / Al weight ratio of 1.6-6, a pH value of 0.5-2.5, and a QP0 2 / QP0 0 is 1-5, among which, QP0 2 Indicated by 31 The chemical shift of the phosphorus aluminum binder obtained by P nuclear magnetic resonance spectroscopy is 12±2ppm, QP0 0 Indicates the resonance signal peak area with a chemical shift of 0±2ppm; the average particle size of the phosphorus aluminum binder is 10-30nm; The silicon-aluminum inorganic binder is obtained by reacting a second aluminum-based binder and a silicon-based binder in a weight ratio of (1-50):1, wherein the second aluminum-based binder is calculated as Al2O3 and the silicon-based binder is calculated as SiO2.

2. The catalytic cracking catalyst promoter according to claim 1, wherein The straight tube wear index of the catalytic cracking catalyst promoter is 0-2% / h; the thermal wear index is 0-8% / h.

3. The catalytic cracking catalyst promoter according to claim 1, wherein Based on the dry weight of the catalytic cracking catalyst promoter, the content of the MFI molecular sieve is 15-65% by weight, the content of the phosphorus aluminum binder calculated as P2O5 and Al2O3 is 8-32% by weight, the content of the silicon aluminum inorganic binder calculated as SiO2 and Al2O3 is 2-20% by weight, the content of the first aluminum-based binder is 2-10% by weight, and the content of the clay is 1-20% by weight.

4. The catalytic cracking catalyst promoter according to claim 1, wherein The phosphoaluminum binder contains 3-12 wt% Al2O3, 15-32 wt% P2O5 and 0.5-5 wt% stabilizer, the P / Al weight ratio of the phosphoaluminum binder is 1.7-5.8, the pH value is 0.5-2.5, QP0 2 / QP0 0 It is 1.5-5.

5. The catalytic cracking catalyst promoter according to claim 1, wherein The first aluminum-based binder and the second aluminum-based binder are independently selected from one or more of pseudo-boehmite, acidified aluminum stone and aluminum sol; the silicon-based binder includes acidic silica sol; The clay is selected from one or more of kaolin, sepiolite, attapulgite, rectorite, montmorillonite and diatomaceous earth; The MFI molecular sieve is one or more selected from hydrogen-type MFI molecular sieve, phosphorus-containing MFI molecular sieve and transition metal-containing MFI molecular sieve.

6. A method for preparing the catalytic cracking catalyst promoter according to any one of claims 1 to 5, the method comprising: S1, mixing the second aluminum-based binder and the silicon-based binder and slurrying them, and aging them at 50-90° C. for 30-60 min to obtain a silicon-aluminum inorganic binder; S2, mixing and slurrying the silicon-aluminum inorganic binder, MFI molecular sieve, optional clay, the first aluminum-based binder and water, controlling the pH value of the obtained first slurry to be 2-5, and obtaining a second mixture; S3, mixing the second mixture with a phosphorus aluminum binder and slurrying, spray drying and calcining the obtained second slurry to obtain the catalytic cracking catalyst promoter.

7. The method according to claim 6, wherein: The aluminum-phosphorus binder is prepared by a method comprising the following steps: (1) mixing an aluminum source, water and a stabilizer at a temperature of 50-95° C. and stirring to obtain an aluminum oxide precursor solution having a solid content of 5-40% by weight; (2) Mixing and reacting the alumina precursor solution with phosphate at a temperature of 25-70° C. and under stirring conditions to obtain the phosphate-aluminum binder.

8. The method according to claim 7, wherein: In step (1), the weight ratio of the aluminum source, water and stabilizer is 100:(50-800):(5-40), preferably 100:(100-750):(6-35), and the aluminum salt is calculated as aluminum oxide; In step (2), the weight ratio of the aluminum oxide precursor solution to the phosphate is 100:(50-200), preferably 100:(60-150), and the phosphate is calculated as phosphorus oxide.

9. The method according to claim 7, wherein: The aluminum source is selected from one or more of aluminum nitrate, aluminum sulfate and aluminum chloride; The phosphate is diammonium hydrogen phosphate and / or ammonium dihydrogen phosphate; The stabilizer is selected from one or more of acetic acid, glycolic acid, oxalic acid, malonic acid, malic acid, tartaric acid, succinic acid, adipic acid, maleic acid, itaconic acid and citric acid, preferably acetic acid or citric acid.

10. A method for catalytic cracking of hydrocarbon oil, the method comprising: The hydrocarbon oil is contacted with a catalyst for reaction, wherein the catalyst contains the catalyst promoter according to any one of claims 1 to 5.

11. The method according to claim 10, wherein: The conditions for the catalytic cracking reaction of hydrocarbon oil include: a temperature of 400-600°C, a weight hourly space velocity of 8-120 hours -1 , the agent-oil weight ratio is 1-20.

Citation Information

Patent Citations

  • Cracking aid for improving lower-carbon olefin concentration

    CN102847552A

  • Cracking auxiliary agent for increasing low-carbon olefin concentration

    CN103785456A

  • Catalytic cracking aid for increasing propylene yield, and preparation method thereof

    CN107970982A

  • Phosphorus-containing rare-earth-containing MFI structure molecular sieve rich in mesopore, preparation method, and catalyst containing same and application thereof

    EP3868471A1

  • Multi component catalyst and its use in catalytic cracking

    US20050070422A1